2020
DOI: 10.1097/md.0000000000021417
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone for preventing postoperative nausea and vomiting after mastectomy

Abstract: Background: Postoperative nausea and vomiting (PONV) is a common complication after mastectomy. Although many researches have been studied the prophylactic effect of antiemetics, none of the results are effective. To overcome this problem, dexamethasone was used to relieve the occurrence of PONV. Since concerns about steroid-related morbidity still remain, We carried out a meta-analysis to evaluate the impact of prophylactic dexamethasone on PONV, post-operative pain undergoing mastectomy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
(55 reference statements)
0
5
0
1
Order By: Relevance
“…Tenghui Zhang et al [ 20 ] found that a single dose of 8mg dexamethasone can effectively reduce postoperative pain and shorten hospital stay. Leilai Xu et al [ 21 ] reported that dexamethasone can not only reduce the incidence of PONV, but also reduce postoperative pain. It is reported by Elizabeth A Klag et al [ 22 ] that dexamethasone can effectively control the occurrence of postoperative pain, nausea and vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…Tenghui Zhang et al [ 20 ] found that a single dose of 8mg dexamethasone can effectively reduce postoperative pain and shorten hospital stay. Leilai Xu et al [ 21 ] reported that dexamethasone can not only reduce the incidence of PONV, but also reduce postoperative pain. It is reported by Elizabeth A Klag et al [ 22 ] that dexamethasone can effectively control the occurrence of postoperative pain, nausea and vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a high incidence of post-operative nausea and vomiting has been found in patients with MRM, and the use of opioids and NSAIDs may increase the incidence of postoperative nausea and vomiting. 15 Transdermal patch is a non-invasive method of providing post-operative analgesia and has been found to be very effective in reducing pain scores in the post-operative period in various other surgeries. But transdermal patches generally contain opioids and NSAIDs, which can again increase the incidence of nausea and vomiting after MRM surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative dexamethasone is effective to reduce the pain, nausea and vomiting after thyroid surgery, which was reported by Cheng et al [ 29 ]. Some studies have reported [ 30 ] not only does Dexamethasone reduce the incidence of PONV but also decreases postoperative pain. Because of this, we speculated that dexamethasone may also have very good safety and efficacy in controlling post-embolization syndrome after TACE.…”
Section: Discussionmentioning
confidence: 99%